A new pricing approach for SME loans issued by commercial banks based on credit score mapping and Archimedean Copula simulation - Liu, Chang; Shi, Haoming; Cai, Yujun; Shen, Shu; Lin, Dongtao (Journal of Business Economics and Management, 2019)
The traditional loans pricing methods are usually based on risk measures of individual loan’s characteristics without considering the correlation between the defaults of different loans and the contribution of individual loans to the entire loan portfolio. In this study, using account-level loans data of 2010-2016 abstracted from 2 databases kindly provided by a Chinese commercial bank, the authors choose Archimedean Copula to fit the default relationship between loans, combined with the loss distribution function constructed to measure the economic capital of the loan portfolio, to propose a loan pricing method that is more suitable for measuring the unique risk characteristic of SMEs loans. Empirical evidence shows that compared with the traditional loan pricing model, this new proposed one, requiring lower loan interest rates from customers with higher credit rating, while higher loan interest rates from customers with lower credit rating, could thus be able to provide higher risk-adjusted returns, higher economic capital adequacy ratios, and ultimately stronger banks’ capabilities to tolerate risk events. Although there might still be some issues and limitations in the study, the method proposed in this study could be of interest not only to the banks’ management, but also to banking regulators as well.